PENDAMPINGAN PEMASARAN UMKM MENGGUNAKAN MEDIA SOSIAL - Narwanto, Narwanto (Adi Widya : Jurnal Pengabdian Masyarakat, 2024)
Assistance in the use of social media for Micro, Small and Medium Enterprises (MSMEs) provides advantages and convenience in carrying out promotions to increase sales volume. The method used in community service is introduction, creation and assistance by choosing the right application is TikTok Shop. The TikTok Shop platform merges with TikTok as a TikTok platform that can share short videos without any time limits and has a wide reach and network with high traffic. The advantages of the TikTok Shop are expected to be able to help Mui Cat Shop to increase sales volume so that the expected profit is achieved.